SMALL INDUSTRIAL ZONES: CATALYSTS FOR LOCAL ECONOMIC GROWTH AND DEVELOPMENT ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Small industrial zones play a pivotal role in fostering economic growth and development at the local level. This scientific article explores the significance of small industrial zones, their impact on regional economies, and the factors contributing to their success. Through an analysis of case studies and empirical evidence, we investigate the key drivers behind the establishment and sustainability of these zones. The article also discusses the challenges faced by small industrial zones and the potential strategies to overcome them. By understanding the dynamics of small industrial zones, policymakers, investors, and communities can better harness their potential to drive economic prosperity.